Effect of Optic Canal Opening on Postoperative Visual Acuity in Patients with Tuberculum Sellae Meningiomas - Chen, Lihua; Gao, Mou; Zhang, Hongtian; Chen, Wenjin; Sun, Kai; Xu, Ruxiang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Tuberculum sellae meningiomas (TSMs) account for 5 to 10% of all intracranial meningiomas. They typically invade the optic canal and displace the optic nerve upward and laterally. The transcranial approach has been the standard surgical approach, while the transsphenoidal approach has been proposed for its minimally invasive nature; however, some reservations concerning this approach remain.Methods From January 2000 to December 2018, a total of 97 patients who were diagnosed with TSM with invasion of the optic canal were enrolled and underwent microsurgery for tumor removal with optic canal opening. A retrospective analysis was performed on the effect of optic canal opening on postoperative visual acuity improvement. The median follow-up was 17.4 months (range: 3–86 months).Results Among the 97 patients with TSM involving the optic canal, optic canal invasion was seen on preoperative imaging in 73 patients and during intraoperative exploration in all patients. In total, 87/97 patients (89.7%) underwent optic canal opening to remove tumors involving the optic canal, and the rate of total macroscopic resection of tumors invading the optic canal was 100%. Among the 10 patients who did not undergo optic canal opening, the rate of total resection of tumors involving the optic canal was 80% (8/10, p < 0.001). There were no deaths or serious complications. The postoperative visual acuity improvement rate was 64.4%, 23.7% maintained the preoperative level, and the visual acuity deteriorated 11.9%.Conclusion Intraoperative optic canal opening is the key to total resection of TSMs involving the optic canal and improving postoperative visual acuity.
Keywords: tuberculum sellae; meningioma; optic canal; visual acuity